Romanian-Hungarian Conflict in Targu-Mures/ Marosvasarhely in March 1990 (Romania, 1990)
Amateur footage (although some of them could have been taken by local TV crew) made during the escalating conflict between Hungarians and Romanians in Targu-Mures/Marosvásárhely in March 1990. Most of the footage is unedited and covers the events and opinions on both sides of the conflict. Some footage covers the pre-history of the conflict with images from the Revolution of 1989 in Targu-Mures/Marosvásárhely and some events in February 1990 in the same city, all related to the emerging ethnic conflict.